2021
DOI: 10.3389/fnut.2021.667466
|View full text |Cite
|
Sign up to set email alerts
|

Magnitudes of Anemia and Its Determinant Factors Among Lactating Mothers in East African Countries: Using the Generalized Mixed-Effect Model

Abstract: Background: The number of studies on the magnitude of anemia and its determinant factors among lactating mothers is limited in East African countries regardless of its multivariate consequences. Even though few studies were conducted on the magnitude of anemia and its determinants, most of them focused on the country level and different parts of countries. Therefore, the current study is aimed to determine the magnitude of anemia and determinant factors among lactating mothers in East African countries.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 16 publications
3
11
2
3
Order By: Relevance
“…The prevalence of anaemia in this study is however lower than the prevalence reported in East Africa 36.5%, 18 Myanmar 73.8%, 8 India 62.9%, 9 Binjai in Indonesia 52%, 22 Ethiopia,43% 23 and Somalia 48.7%. 11 The lower prevalence of anaemia could be attributed to geographical location, feeding habits, differences in sample size and socioeconomic status of these lactating mothers in these studies compared to ours.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…The prevalence of anaemia in this study is however lower than the prevalence reported in East Africa 36.5%, 18 Myanmar 73.8%, 8 India 62.9%, 9 Binjai in Indonesia 52%, 22 Ethiopia,43% 23 and Somalia 48.7%. 11 The lower prevalence of anaemia could be attributed to geographical location, feeding habits, differences in sample size and socioeconomic status of these lactating mothers in these studies compared to ours.…”
Section: Discussioncontrasting
confidence: 80%
“…Anaemia in lactating mothers remains a public health burden affecting both the mother and the newborn. 18 We determined the prevalence and risk factors of anaemia among lactating mothers at Mbarara City Health Centre IV (MCHC-IV). The overall prevalence of anaemia among lactating mothers was 24.6%.…”
Section: Discussionmentioning
confidence: 99%
“…16 However, this prevalence is far lower than the prevalence of anemia among lactating women in India (63%) 32 and higher than that in East Africa (36.15%). 27 The increased prevalence of anemia among lactating women in this study as compared to the prevalence of anemia among the entire population of women in the reproductive age group could be due to the additional nutrition requirements (including iron requirements) needed for the production of adequate quantity of milk, whereas the difference between the prevalence of anemia in this study and that among lactating women in India could be attributed to the study population, time gap and study setting among others.…”
Section: Discussionmentioning
confidence: 65%
“…This is in-line with a study carried out in East Africa. 27 This is not surprising as these women never got the opportunity to receive services offered by the field (health) workers. The field (health) workers offer health education, referral and follow-up of the lactating women within their communities as part the routine outreaches, they carry out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation